PRINCIPLES OF 3-DIMENSIONAL HYDROGEOLOGICAL MODELING AND ITS APPLICATION ON THE PATTERN OF YEREVAN DEPRESSION (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
The principles of three-dimensional groundwater modeling are considered in the article. It is noted that the basic program of groundwater flow simulation was developed by McDonald M. and Harbaugh A.W., which is called Modflow. In this paper on the basis of lithological sections of the wells drilled in Yerevan Basin the transition from lithologic layers to generalized layers on their permeability has been conducted, i.e. layers with similar permeability properties are linked in a single layer. As a result, for Yerevan Basin three layers have been obtained: water-bearing, confined and slowly permeable.
Keywords: Modflow; Win Flow; hydrogeological modeling; 3D modeling; water supply systems